Transcriptome analysis of peripheral blood of Schistosoma mansoni infected children from the Albert Nile region in Uganda reveals genes implicated in fibrosis pathology. - Joyce Namulondo; Oscar Asanya Nyangiri; Magambo Phillip Kimuda; Peter Nambala; Jacent Nassuuna; Moses Egesa; Barbara Nerima; Savino Biryomumaisho; Claire Mack Mugasa; Immaculate Nabukenya; Drago Kato; Alison Elliott; et al. (Public Library of Science (PLoS), 2023)
Over 290 million people are infected by schistosomes worldwide. Schistosomiasis control efforts focus on mass drug treatment with praziquantel (PZQ), a drug that kills the adult worm of all Schistosoma species. Nonetheless, re-infections have continued to be detected in endemic areas with individuals living in the same area presenting with varying infection intensities. Our objective was to characterize the transcriptome profiles in peripheral blood of children between 10-15 years with varying intensities of Schistosoma mansoni infection living along the Albert Nile in Uganda. RNA extracted from peripheral blood collected from 44 S. mansoni infected (34 high and 10 low by circulating anodic antigen [CAA] level) and 20 uninfected children was sequenced using Illumina NovaSeq S4 and the reads aligned to the GRCh38 human genome. Differential gene expression analysis was done using DESeq2. Principal component analysis revealed clustering of gene expression by gender when S. mansoni infected children were compared with uninfected children. In addition, we identified 14 DEGs between S. mansoni infected and uninfected individuals, 56 DEGs between children with high infection intensity and uninfected individuals, 33 DEGs between those with high infection intensity and low infection intensity and no DEGs between those with low infection and uninfected individuals. We also observed upregulation and downregulation of some DEGs that are associated with fibrosis and its regulation. These data suggest expression of fibrosis associated genes as well as genes that regulate fibrosis in S. mansoni infection. The relatively few significant DEGS observed in children with schistosomiasis suggests that chronic S. mansoni infection is a stealth infection that does not stimulate a strong immune response.